Monetary Policy Matters : New Evidence Basedon a New Shock Measure - Crowe, Christopher (IMF Working Papers; Working Paper ;, 2010)
Conventional VAR and non-VAR methods of identifying the effects of monetary policy shocks on the economy have found a negative output response to monetary tightening using U.S. data over the 1960s-1990s. However, we show that these methods fail to find this contractionary effect when the sample is restricted to the period since the 1980s, apparently due to changes in the policymaking environment that reduce their effectiveness. Identifying policy shocks using Fed Funds futures data, we recover the contractionary effect of monetary tightening on output and find that almost half of output variation over the period appears due to policy shocks.